The Post-Truth Phenomenon On Social Media In The Perspective Of The Qur'an: A Study Of Tafsir Al-Kasysyaf By Az-Zamakhsyari - Musholli; Abdul Karim (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study examines the post-truth phenomenon on social media from the Qur'anic perspective using Al-Kasysyaf by Az-Zamakhshari as the primary interpretive framework. Unlike previous studies that mainly discuss post-truth from the perspectives of communication, politics, or normative Islamic ethics, this study highlights the novelty of Al-Kasysyaf as an epistemological framework for interpreting contemporary digital information disorders. A qualitative library research approach combined with digital content analysis was employed to analyze the relationship between post-truth practices and Qur'anic principles of information ethics. The findings reveal three main points. First, there is a significant gap between the Qur'anic principle of tabayyun and digital practices that prioritize virality over factual verification. Second, the Qur'an promotes critical reasoning and epistemic responsibility in receiving and disseminating information. Third, Qur'an-based digital literacy, interpreted through Al-Kasysyaf, provides an ethical framework for preventing hoaxes and disinformation while maintaining social integrity. This study contributes theoretically by extending the application of classical Qur'anic exegesis to contemporary digital communication and practically by providing a conceptual foundation for educators, digital media users, and policymakers in promoting ethical and responsible digital communication.